Factors Affecting Investment Decisions in Nepali Stock Market: A Systematic Review - Lamichhane, Baburam (Pargatishil Darpan, 2024)
The study examines factors influencing investment decisions in the Nepali stock market. It employs a thorough review methodology, drawing on past research across various stock market conditions. By analyzing relevant concepts, findings, and conclusions from these studies, it provides insights specific to the Nepali context. Key factors identified include market environment, investment motives, information availability, third-party opinions, the company's reputation, and herding behavior. The study highlights the importance of aligning investment strategies to achieve both long-term gains and short-term profits. Additionally, it emphasizes the need for diversification by building an investment portfolio to mitigate risks and enhance returns in the Nepali stock market.